The day the Earth stood still - Derrickson, Scott; Reeves, Keanu; Connelly, Jennifer; Smith, Jaden, 1998-; Cleese, John; Hamm, Jon, 1971-; Chandler, Kyle; Bates, Kathy, 1948-; Twentieth Century-Fox Film Corporation; Dune Entertainment; 3 Arts Entertainment (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2009)
Governments and scientists race to unravel the mystery behind a visitor's appearance. Dr. Helen Benson finds herself face-to-face with an alien who has traveled across the universe to warn of an impending crisis. She quickly discovers the deadly ramifications of Klaatu's claim that he is a 'friend to the Earth.' Now, she and her young stepson must find a way to convince the entity who was sent to destroy humans that mankind is worth saving, but it may be too late.
Videodisc release of the 2008 motion picture.
Based on the screenplay by Edmund H. North.
Keanu Reeves, Jennifer Connelly, Jaden Smith, John Cleese, Jon Hamm, Kyle Chandler, Kathy Bates.
MPAA rating: PG-13; for some sci-fi disaster images and violence.
DVD, widescreen.
In English with optional French or Spanish dubbing and English or Spanish subtitles; closed captioned for the hearing impaired.
Keywords: Human-alien encounters -- Drama; Women scientists -- United States -- Drama; Extraterrestrial beings -- Drama; Military robots -- Drama; Nature -- Effect of human beings on -- Drama; Human beings -- Drama; Mothers and sons -- United States -- Drama; Video recordings for the hearing impaired; Science fiction films